TRAINING ON THE PREPARATION OF VIRGIN COCONUT OIL (VCO)S BUSINESS PROPOSAL IN SMALL, MEDIUM COMMUNITIES (MSMES) IN GAMPONG LAM NEUHEUN, KUTA BARO, ACEH BESAR - Febyolla Presilawati; Emmi Suryani; Intan Rizkia Chudri; Fitri Yunina (Universitas Muhammadiyah Aceh, 2022)
Training on the preparation of Virgin Coconut Oil (VCO) business proposals for Micro, Small and Medium Enterprises (UMKM) is a learning process in business proposals to obtain grants from government agencies or social institutions for business progress. In order to achieve this goal, community service was carried out in the form of training in the preparation of VCO business proposals for UMKM in Lam Neuhen Village, Kuta Baro, Aceh Besar. This method is done by training for one day and a duration of 4 hours. The material presented by the presenters is by way of presentation, discussion, and case examples. In general, this implementation is in the category of success. Participants seen from the responses shown. The implementation of this community activity is on schedule, attended by a large number of participants, and is supported by good facilities, mastery of the material and the ability to deliver good material to participants.Keywords: Training, Service, Proposal, UMKM, VCO